2001
DOI: 10.1055/s-2001-18034
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Metabolic Abnormalities Involved in Obesity [nl]Associated with Typical Antipsychotic Drug Administration

Abstract: In this study, the authors assessed the endocrine system and glucose tolerance in obese and non-obese women chronically treated with typical antipsychotic drugs (AP). In particular, we tested the hypotheses that these subjects display hypogonadism and increased insulin resistance compared to healthy weight-matched controls, as these abnormalities create a tendency towards excessive body weight gain. Twenty-six AP-treated women were matched with 26 healthy women by age, body mass index and day of the menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…These studies indicate conclusively that, when matched appropriately with nonpsychiatric subjects, patients with schizophrenia do not exhibit greater than expected serum leptin levels regardless of antipsychotic drug exposure (Baptista et al, 2001;Eder et al, 2001;Herran et al, 2001;Hagg et al, 2001;Zhang et al, 2003;Arranz et al, 2004;Sporn et al, 2005;Haupt et al, 2005;Gergerlioglu et al, 2006;Atmaca et al, 2007). The one controlled comparative study of medication-treated bipolar patients vs. matched controls also reported no significant difference in leptin levels between the psychiatric patients and their peers (Gergerlioglu et al, 2006).…”
Section: Diagnosis Effectsmentioning
confidence: 75%
See 1 more Smart Citation
“…These studies indicate conclusively that, when matched appropriately with nonpsychiatric subjects, patients with schizophrenia do not exhibit greater than expected serum leptin levels regardless of antipsychotic drug exposure (Baptista et al, 2001;Eder et al, 2001;Herran et al, 2001;Hagg et al, 2001;Zhang et al, 2003;Arranz et al, 2004;Sporn et al, 2005;Haupt et al, 2005;Gergerlioglu et al, 2006;Atmaca et al, 2007). The one controlled comparative study of medication-treated bipolar patients vs. matched controls also reported no significant difference in leptin levels between the psychiatric patients and their peers (Gergerlioglu et al, 2006).…”
Section: Diagnosis Effectsmentioning
confidence: 75%
“…Several antipsychotic studies measured metabolic outcomes along with serum leptin levels, but did not specifically calculate correlation coefficients between leptin and other parameters (Baptista et al, 2001;Eder et al, 2001;Atmaca et al, 2003a;Melkersson and Dahl, 2003;Graham et al, 2005a;Graham et al, 2005b;Smith et al, 2005;Sporn et al, 2005;Chiu et al, 2006;Hosojima et al, 2006;Atmaca et al, 2007). Nonetheless, in many instances leptin levels increased significantly without significant changes in serum insulin, other glycemic or lipid measures (Zhang et al, 2004;Murashita et al, 2005;Sporn et al, 2005;Chiu et al, 2006;Hosojima et al, 2006;Atmaca et al, 2007).…”
Section: Other Metabolic Parametersmentioning
confidence: 99%
“…Moreover, this study used a minimal (3-day) washout period before OLZ treatment for the large number of subjects with prior treatment history with other antipsychotics. Induction of central obesity by atypical antipsychotics has also been inferred from cross-sectional studies (44,45) reporting waist-to-hip ratios. Clearly, the present studies are unique in that they provide the first accurate measures of adiposity during antipsychotic treatment and support the idea that adiposity may be increased considerably more than is reflected in body weight alone.…”
Section: Discussionmentioning
confidence: 99%
“…This fall in HDL levels after these drugs is in concordance with majority of the studies. [27][28][29] When comparing the number of subjects fulfilling the criteria for raised HDL-C (as per MS-IDF) criteria, it was found that in olanzapine group, 3 subjects met the criteria before intervention and the number increased to 10. On the other hand in risperidone group, the number of subjects fulfilling the raised HDL-C criteria increased from 4 to 7.…”
Section: As Per the International Diabetes Federation (Idf 2006) Critmentioning
confidence: 99%